Proceedings of the XIII Internarional Conference on Ground Penetrating Radar 2010
DOI: 10.1109/icgpr.2010.5550193
|View full text |Cite
|
Sign up to set email alerts
|

Impact of spatial sampling and antenna polarization on 3D GPR fracture detection

Abstract: Three-dimensional Ground Penetrating Radar (3D GPR) surveys are needed to reconstruct subsurface fracture networks in terms of strike, dip and interconnectivity. This particular GPR study conducted in the Madonna della Mazza quarry (Italy) compares the impact of a dense acquisition grid versus antenna polarization on the characterization of subvertical fractures. 3D GPR data were acquired using a 250 MHz antenna over a 20x20m area with a grid bin size of 5x5cm. According to the quarter-wavelength criterion, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…When the intervals of two dimensional scan of GPR are less than quarter wavelength of transmitting signal in the dielectric media, the subsurface 3D image with high quality can be obtained. Marchesini and Grasmuech [4] concluded that, rather than the antenna orientation, the regular and highly sampled acquisition grid for 3D GPR survey was more important for highresolution characterization of 3D fracture frameworks. But this conclusion is not proper for detecting the hidden cylinders with different orientations in the same way.…”
Section: Measurement Configurationmentioning
confidence: 99%
“…When the intervals of two dimensional scan of GPR are less than quarter wavelength of transmitting signal in the dielectric media, the subsurface 3D image with high quality can be obtained. Marchesini and Grasmuech [4] concluded that, rather than the antenna orientation, the regular and highly sampled acquisition grid for 3D GPR survey was more important for highresolution characterization of 3D fracture frameworks. But this conclusion is not proper for detecting the hidden cylinders with different orientations in the same way.…”
Section: Measurement Configurationmentioning
confidence: 99%
“…When this is applied to our prospection in Ammaia, with average subsurface velocities of ~0.065 m ns −1 (areas 1A and 1B, surveyed in November 2010 in east–west and north–south directions, respectively, and partially overlapping; Figure ) and ~0.1 m ns −1 (area 2, surveyed in July 2011), and given the nominal centre frequency of the antennae (500 MHz), the transect spacing should be smaller than 0.0325 m and 0.05 m, respectively. In addition, the useful GPR signal contains frequency components significantly higher than the centre frequency of the antenna (Davis and Annan, ), which would reduce the profile spacing even further (Marchesini and Grasmueck, ).…”
Section: Determining the Transect Spacingmentioning
confidence: 99%
“…The 8 m wide rim between pond wall and 3D GPR survey edge allows lateral movement of the infiltrated water and is also necessary for the 3D migration aperture, especially at larger depths. The 0.05 m line spacing was chosen in order to properly sample the higher than 200MHz frequency content of the GPR antennae [2,7].…”
Section: The 4d Gpr Monitored Infiltration Experimentsmentioning
confidence: 99%